PROSA, RUANG, DAN KOTA PASCAKOLONIAL - Moh. Atikurrahman (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Today, the studies on post-colonial urban space in relation with Indonesian modern prose can be said to be minimal. On the other hand, in the history of Indonesian literature, we are endowed with writers like Armijn Pane, Idrus, Pramoedya Ananta Toer, Iwan Simatupang, Budi Darma etc., who consistently write prose with the background of the ex-colonial towns. Unfortunately, there is no enough studies of the encounter between those writers with the city as a representation of a post-colonial experience. This paper tried to track the integral relationship between Indonesian modern prose writers to the city by using the spatial space theory in relation to the study of post-colonial literature in Indonesia. This analysis used the spatial theory by Sara Upstone as the approach, especially regarding to space (spatial) city.Keywords: spatial, city, postcolonial.